Differential absorbance study of interactions between europium, soil and aquatic NOM and model compounds. (November 2019) - Chen, Yao; Fabbricino, Massimiliano; Luongo, Vincenzo; Korshin, Gregory V.
Abstract: This study compared the binding of europium by soil and aquatic natural organic matter (NOM) exemplified by Pahokee Peat humic acid (PPHA) and Northern Reservoir NOM, respectively. NOM/Eu 3+ interactions were measured based on the differential absorbance approach. The experimental results show that the binding of Eu 3+ by humic acid isolated from agricultural soil results in several features of the differential spectra that are distinct from those observed for aquatic NOM. These features may be associated with the presence in soil NOM of functional groups similar to gallic acid. The binding of Eu 3+ by NOM was modeled using a phenomenological approach that accounted for the involvement of dissimilar metal-binding functionalities. This study also introduced the concept of integrated differential absorbance; the use of that parameter allowed achieving a close fit between the experimental and model data. This study presents an alternative approach to ascertain mechanisms of, and differences in the interactions of europium with model compounds and natural organic matter with the provenance from soil and surface water. Graphical abstract: Image 1 Highlights: Eu-binding functionalities prevalent in aquatic and soil NOM are different Gallic acid can be used as model compound for aquatic NOM Quercetin can be used as model compound for soil NOM Eu-complexation can be modeled considering two types of binding sites Integrated differential absorbance is an indirect measure of Eu bound to NOM